2000
DOI: 10.1136/heart.83.6.661
|View full text |Cite
|
Sign up to set email alerts
|

Arrhythmias in the congenital long QT syndrome: how often is torsade de pointes pause dependent?

Abstract: Objective-To determine the frequency and predictors of pause dependent torsade de pointes among patients with the congenital long QT syndrome and spontaneous ventricular tachyarrhythmias. Design-The literature on the "congenital long QT" was reviewed. Articles with illustrations demonstrating the onset of spontaneous polymorphic ventricular arrhythmias in the absence of arrhythmogenic drugs were included. Results-Illustrations of 62 spontaneous episodes of torsade de pointes among patients with congenital long… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
60
1

Year Published

2003
2003
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(68 citation statements)
references
References 71 publications
7
60
1
Order By: Relevance
“…In contrast to previous studies, 21 we did not find that the proportion of pause dependence was greater in female than male patients.…”
Section: Discussioncontrasting
confidence: 56%
See 2 more Smart Citations
“…In contrast to previous studies, 21 we did not find that the proportion of pause dependence was greater in female than male patients.…”
Section: Discussioncontrasting
confidence: 56%
“…37 Also, because ␤-blocker treatment is less effective in LQT2, TdP may still be readily observed during admission. Whatever the cause, the difficulty in obtaining ECG documentation of TdP onset in LQT1 may explain why the reported proportion of pause-dependent TdP onset in congenital LQTS is as high as 74% in some studies, 21 although it should be only a little over 50%, given that TdP is rarely pause dependent in LQT1 and that LQT1 constitutes almost 50% of congenital LQTS. This discrepancy may be caused by underrepresentation of LQT1 patients because these patients are less easily included in such analyses.…”
Section: Study Limitationsmentioning
confidence: 96%
See 1 more Smart Citation
“…In myocytes isolated from mice heterozygous for a knock-in KPQ deletion (⌬KPQ), diastolic arrhythmogenic activity is significantly more prevalent than in myocytes isolated from WT littermates. Because pause-dependent arrhythmias were previously reported in ECG measurements in these mice, 11 and because clinical, in vivo animal and computational studies have demonstrated correlation between the spontaneous arrhythmias in LQTSs following pauses in stimulation, 26,27 we focused our studies on pause-dependent activity that might occur in myocytes. Our results show that even in WT myocytes, prolonged depolarization can lead to spontaneous activity (I TI s).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, dAPC data on the A1330P mutant give an insight into the mechanism underlying AP prolongation and arrhythmogenesis in the carrier of this mutation. Facilitated (re)openings of the cardiac sodium channels due to mutation are likely to cause a rise in intracellular Na Literature data suggest that sudden pauses play a major role in the genesis of spontaneous arrhythmias in the congenital LQT syndrome (Viskin et al 2000). Patients with LQT3 are at a greater risk of cardiac events during rest or bradycardia than during exercise when heart rate is elevated Veldkamp et al 2003).…”
Section: Discussionmentioning
confidence: 99%